COMMUNITY DEVELOPMENT THROUGH STRENGTHENING CHARACTER EDUCATION - Rita Sriayu; Zamroni Zamroni; Siti Kamilah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The purpose of this study is to examine the strategic role of character education in the process of developing a sustainable and civilized society. Character strengthening is seen as a moral foundation as well as a social instrument that fosters collective awareness and citizen participation in building an inclusive civilization. The research method uses a library research approach, with a literature selection process based on inclusion criteria (Sinta/Scopus/Garuda indexed journal articles, relevant books, 2019–2025). This article analyzes character education policies in Indonesia, their relationship to local wisdom values, and relevant integration models in the context of a pluralistic society. The results of the study indicate that character strengthening is effective when supported by adaptive public policies, persuasive communication strategies based on wisdom and mau‗idhah hasanah, and collaboration between educational institutions, the government, and local communities. Character education is not merely a cognitive process, but also a social transformation towards a society that is moral, empowered, and just.